2014
DOI: 10.5586/asbp.2014.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix surface network is associated with non-morphogenic calli of Helianthus tuberosus cv. Albik produced from various explants

Abstract: Helianthus tuberosus is economically important species. To improve characters of this energetic plant via genetic modification, production of callus tissue and plant regeneration are the first steps. A new, potentially energetic cultivar Albik was used in this study to test callus induction and regeneration. Callus was produced on leaves, petioles, apical meristems and stems from field-harvested plants but was totally non-morphogenic. Its induction started in the cortex and vascular bundles as confirmed by his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…The cells of the morphogenetic callus were surrounded by a fibrillar structure DNA amplification profiles of plantlets that had been regenerated in vitro (1-19) that were obtained using a RAPD14 primer: 1-8: plantlets that had been regenerated on RCY1 roots, 9-14: on RCY2 roots, 15-18: on RCY3 roots, 19: on RCY4 roots, M-100 bp molecular weight marker similar to the ECM. ECM has been reported in plant tissue cultures of different species and may be formed on the surface of tissue that is cultured under in vitro conditions as a stress response or protective layer against external factors regardless of its morphogenetic competence (Pilarska et al 2014;Ś lesak et al 2014). ECM can also serve as a structural marker of somatic embryogenesis (Namasivayam et al 2006) or organogenesis (Popielarska-Konieczna et al 2008, which was confirmed in our experiments on R. thyrsiflorus, in which we observed a fibrillar structure that surrounded morphogenetic callus cells.…”
Section: Discussionsupporting
confidence: 73%
“…The cells of the morphogenetic callus were surrounded by a fibrillar structure DNA amplification profiles of plantlets that had been regenerated in vitro (1-19) that were obtained using a RAPD14 primer: 1-8: plantlets that had been regenerated on RCY1 roots, 9-14: on RCY2 roots, 15-18: on RCY3 roots, 19: on RCY4 roots, M-100 bp molecular weight marker similar to the ECM. ECM has been reported in plant tissue cultures of different species and may be formed on the surface of tissue that is cultured under in vitro conditions as a stress response or protective layer against external factors regardless of its morphogenetic competence (Pilarska et al 2014;Ś lesak et al 2014). ECM can also serve as a structural marker of somatic embryogenesis (Namasivayam et al 2006) or organogenesis (Popielarska-Konieczna et al 2008, which was confirmed in our experiments on R. thyrsiflorus, in which we observed a fibrillar structure that surrounded morphogenetic callus cells.…”
Section: Discussionsupporting
confidence: 73%
“…Our SEM analysis pattern was in lieu with the findings of Narciso and Hatorri (2010). The extracellular matrix surface network (ECMSN) that was visible in the cell composition of the callus has been extensively discussed by Bevitori et al (2014) and Pilarska et al (2014). Previous reports on similar structures have been published by Xu et al (2011) in banana, Lai et al (2011) in pennyworts and Pilarska et al (2013) in clover.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, ECMSN was observed on the surface of the non-morphogenic calli of Helianthus tuberosus that had been produced from different types of explants by Pilarska et al [34]. These authors hypothesised that the formation of an extracellular net could be related to a stress response and protection against external factors that are specific to the culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pectins are also known to play protective roles in the interactions between plants and phytopathogens [52, 53]. To date, studies on the functions of pectins in monocots are very limited [34, 40, 54, 55]. In their study on androgenic cultures of wheat cultivars, Pilarska et al [56] demonstrated that the xylogalacturonan-targeting LM8 antibody gave signals only in a peripheral cell and that the JIM5 antibody specifically detected methyl ester-rich pectins, in the cell walls of the callus parenchyma, thus suggesting the importance of pectic substances in wheat androgenesis, and possibly in the regulation of cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%